The impact of prostate-specific antigen, its density and the Gleason score in the prediction of extracapsular disease in prostate carcinoma - (:unkn) unknown (KARGER, 1997)
Objective: To evaluate the effectiveness of serum prostate-specific antigen (PSA), PSA density (PSAD), the preoperative Gleason score of transrectal-ultrasonography (TRUS)-guided needle biopsies and the Gleason score of the final histological examination in predicting extracapsular disease in prostate cancer (PCa). Material and Methods: We retrospectively analyzed 32 patients who underwent radical retropubic prostatectomy as the primary treatment for their clinically localized disease. Results: Extracapsular extension was found in 21 patients. In a comparison of different cutoff levels, the best positive predictive values were found for PSA of 20 ng/ml, PSAD of 0.2 and 0.3, a Gleason score of TRUS-guided biopsies of 5 and one of the prostatectomy specimens of 7 with 100, 80 (both), 74 and 95%, respectively. A PSA value higher than 20 ng/ml and a preoperative Gleason score of 7 or higher predicted extracapsular disease with specificity rates of 100 and 91%, respectively. It was noteworthy that there was a statistically significant undergrading in the extracapsular group in the Gleason scores of TRUS-guided biopsies compared to the prostatectomy specimens. Conclusion: PSA levels above 20 ngl mi and/or Gleason scores of 7 or higher in TRUS-guided biopsies are strong indicators of extracapsular extension of PCa.
Keywords: prostate neoplasm; prostate-specific antigen (PSA) density; Gleason score; staging; CLINICAL STAGE; TUMOR VOLUME; CANCER; PCR